KONSTRUKSI IDENTITAS BERDIMENSI KULTURAL PADA ORANG TERKAYA DI INDONESIA VERSI FORBES: Condra Antoni. Politeknik Negeri Batam condra@polibatam.ac.id - condra antoni (BASIS (Bahasa dan Sastra Inggris), 2016)
People use language to construct their identity or identities and narrative is one of the forms of the language use. The narrative functions as a site for enacting what they are, who they are, and how they view the others (Gee, 2011). This paper discusses the identity construction in the narrative of the 2015 richest Indonesian people ranked by Forbes magazine. A discourse analytic approach is employed in this study. The analysis shows that the identity constructions are relevant to the cultural dimensions proposed by Hofstede (1987, 2016) in which the collectivistic culture emerged predominantly in the narrative. Since the data were taken from English narratives in business, the implication for the use of English as a business’ lingua franca is also discussed.